Pengaruh Kepadatan Kandang dan Kebersihan terhadap Tingkat Infeksi Koksidiosis Kelinci di Kecamatan Kembaran Kabupaten Banyumas - Wardani, Ratna Ayu; Indrasanti, Diana; Sufiriyanto, Sufiriyanto (Fakultas Peternakan Universitas Jambi, 2021)
The study aims to determine the effect of cage density and cleanliness on the incidence of coccidiosis as well as to determine the level of coccidiosis infection in Kembaran District, Banyumas Regency. The targets of the research were rabbits raised by rabbit breeders in Kembaran District, Banyumas Regency. Rabbits used consisted of various species and ages by taking into account several criteria of cage density and cleanliness. The research method used was direct observation (survey) with a purposive sampling technique. Samples as many as 90 samples were taken, with each sample consisted of 3 grams of feces. The analysis used is descriptive analysis and Chi Square. The results of the analysis showed that there was an influence between cage density variables on coccidiosis (P<0.05) with X2count>X2table (7.57>3.841) and the influence between cleanliness variables on coccidiosis (P<0.05) with X2count>X2table (35.73>5.991). The total infection rate of rabbit coccidiosis in Kembaran District was 90 %. The rate of coccidiosis infection is non-pathogenic at 46.67 % and pathogenic at 53.33 %. The highest rate of coccidiosis infection was in Karang Tengah Village (40 %), while the lowest coccidiosis infection rate was in Sambeng Kulon Village (16.67 %).